Pengaruh Field Trip Mangrove Cagar Alam Pulau Dua terhadap Sikap Ilmiah Siswa SMA - Dwi Ratnasari; RR Hertien Koosbandiah; Bambang Supriatno (JURNAL EKSAKTA PENDIDIKAN (JEP), 2017)
The aims of this study was to determine the effect of field trip Mangrove Pulau Dua Nature Reserve on the scientific attitude of high school students. The research method is used quasi experiment. On the design using two classes, experimental class and control class. The population is used the students of grade X SMA Negeri A Kota Serang. Data were obtained from a scientific attitude questionnaire calculated using MSI (Methode of Successive Interval) and a questionnaire of teacher and student responses regarding the implementation of learning. The results showed that there was no significant difference of scientific attitude between the experimental class and the control class.